Consciência e atitude ambiental em estudantes de instituições de ensino técnico e tecnológico - Teixeira, Linnik Israel Lima; Silva Filho, José Carlos Lázaro; Meireles, Fernanda Rosalina da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Environmental education is a powerful tool for forming collective environmental awareness from primary school to higher education level. Based on this, this study aims to investigate environmental awareness and environmental behavior among students of a technological educational institution. Using the NEP Scale (Dunlap et al., 2010) through a questionnaire with students it sought to examine the relationship between consciousness and environmental behavior through variables like course, semester, gender and environmental education. The final data generated can be divided into two outcomes: a) environmental awareness, was not observed significant differences between the courses and also for the semesters of respondents. On the other hand, significantly higher levels of environmental awareness were found in women and students who studied environmental education before they enter higher education; b) the environmental behaviour, the highest levels of pro-environmental behavior were found in students of Environmental Engineering, the graduates, on women and college students who studied environmental education before starting higher education. The study results show compliance with other research and suggest area researchers a deepening of the factors that influence these results.